Edukasi Literasi Media Sosial dan Informasi Kesehatan Mental kepada Siswa Madrasah X - Preciosa Alnashava Janitra; Nindi Aristi (Jurnal Gema Ngabdi, 2023)
The number of mental health survivor, especially adolescents in Indonesia, shows an increase. Based on data from Basic Health Research in 2018, around 19 million people experienced mental stability disorders caused by psychic factors, economic factors, nutritional health factors, family factors, and social factors. But there is an interesting fact that the factors of social media use can also cause mental discomfort including: being insecure, closing or even withdrawing, feeling depressed, tremendous stress and so on after reading certain messages on social media. The community service activities that have been carried out focus on Madrasah X students with the aim of being able to increase knowledge and practical literacy skills related to the use of social media, social media ethics, and the selection of good and correct information so that mental health can be maintained positively. Discussion methods, role playing, and tutorials are carried out in this activity. Through this service activity, madrasah students are able to: understand the differences between some social media and the purpose of their use, understand the ethics of social media, and distinguish good and bad information for their mental health